Network News - Quebec Community Groups Network (QCGN) (2023)
Keywords: Official Language Minority Community (OLMC)

Community Vitality & Acceptability of English Canadian Migrants Rated by Québecois Francophone, Acadian and Franco-Ontarian University Students - Bourhis, Richard Y.; Sioufi, Rana; Allard, Réal (QUESCREN Education and Vitality Forum 2023, 2023)

Willingness of Quebec-born Anglophone and Francophone Students to Stay in Quebec or Leave - Bourhis, Richard; Sioufi, Rana (QUESCREN 'Lunch & Learn' Series, 2021)

Profil des jeunes anglophones des Laurentides 15 à 29 ans - 4Korners (2020)
Selon les données publiées par l’Institut de la statistique du Québec en 2020, la population vivant dans les régions administratives de la province a considérablement changé de 2019 à 2021 en raison des répercussions sociales directes de la pandémie de COVID-19 et de ses conséquences sur la migration, la mobilité, l’attractivité de la main-d’oeuvre, la conciliation travail-famille, les habitudes de vie et les loisirs. Ainsi, on estime que 632 000 habitants vivaient dans la région des Laurentides au 1er juillet 2020, marquant une augmentation de 17,7 % pour l’année 2019-2020; ce pourcentage est plus élevé que le taux moyen de l’ensemble de la province (8,5 %) pour cette année. De fait, il est important de souligner que cette région présente la plus forte augmentation depuis le début de la pandémie en mars 2020.

Profile of Laurentian English-speaking Youth 15-29 - 4Korners (2020)
According to data published by the Institut de la statistique du Québec in 2020, the population living in the administrative regions of the province has significantly changed between 2019 and 2021, being directly affected by the social impacts caused by the COVID-19 pandemic and its implications for out-migration, mobility, workforce attractivity, work/life balance, lifestyle habits and leisure activities. As a result, it is estimated that 632,000 inhabitants were living in the Laurentian region as of July 1, 2020. This represents an increase of 17.7% for the year 2019-2020, which is higher than the average rate across the province (8.5%) for that year. In fact, it is important to highlight that this region presents the largest increase since the outbreak of the pandemic in March 2020.